Dynamics of Student Internship System in Faculty of Art of KNUST, Kumasi, Ghana: Exploring Perceptions, Values, Access and Development Outcomes - A., Fening, P.; K., Agyei, I.; K., Howard, E.; K., Asinyo, B. (Indonesian Academy of Social and Religious Research (IASRR), 2023)
An internship programme is a great way to connect what is learnt in class with actual work experience. Existing research has underscored the positive contribution of internship to the educational process and career outcomes among students. The internship programme for students of Faculty of Art, KNUST is a requirement or considered as a compulsory 15 credit hour course for the award of undergraduate degree. As such it is a vital component of the curriculum. Nonetheless, empirical literature on the dynamics of the internship programme at the university is sparse. Without insight into these dynamics however, there will be lack of information that could inform policy and continuous improvement of the programme. To bridge this gap, this paper seeks to analyze the internship experiences of students to determine what factors seem to create the greatest perceived value. The study employed the descriptive exploratory study design approach. Data was obtained from a total of 376 students of the Faculty of Art through the use of questionnaire designed in open and close ended patterns and focus discussions. The statistical package for the social sciences (SPSS) computer package was used for data analysis, while descriptive statistical tools such as frequency and percentage were used to analyze the facts sought from the questionnaire. The students described a variety of skills learned during the internship including mastering the use of some equipment, software, and report writing. About 80% of the participants indicated that the internship programme was important and linked the classroom work to real work environment. All the students regardless of their experiences indicated they had value for the internship which they believe will play a role in their future career objectives. On the other hand, some of the students had some unfavourable experiences including inadequate work space, provision of inadequate PPEs, boring and difficult tasks. Others were engaged in other duties that were not related to their field of studies, all of which could potentially influence the perception of students.